Magnetic field line tracing calculations in divertor region of torsatron Uragan-2M - Rudakov, V.A. (Вопросы атомной науки и техники, 2007)
Torsatron Uragan-2M magnetic configuration in a divertor region was studied at different values of the factor Kφ. Kφ is the ratio between helical field Bh and total toroidal magnetic field B0 (Kφ = Bh/ B0). Values Kφ were changed in the interval 0.2 < Kφ < 0.6. In the cases of large Kφ values, when the closed magnetic configuration is placed inside the vacuum chamber without intersection with the wall, the footprints of outgoing field lines formed two helical lines on the vacuum chamber walls, situated between helical windings. At the small values of Kφ, when the closed magnetic configuration intersects the chamber wall, the external field lines form wide strips, which correspond to the helical trajectories of the magnetic configuration tops. Проведено числове дослідження диверторних потоків у торсатроні Ураган-2М. Вивчені конфігурації магнітного поля при різних співвідношеннях між гвинтовим і продольним магнітним полями 0.2 < Kφ < 0.6. Показано, що у разі великих значень параметру Kφ, коли замкнута магнітна конфігурація повністю розміщується у нутрі вакуумної камери без пересічення зі стінкою, сліди силових ліній, що виходять, створюють на стінці камери дві гвинтові лінії, розміщені між полюсами гвинтової обмотки. У разі малих значень Kφ, коли замкнута магнітна конфігурація пересікає стінку камери, зовнішні силові лінії створюють широку смугу у вигляді гвинтової лінії, вздовж якої проходе вершина магнітної конфігурації. Проведено численное исследование диверторных потоков в торсатроне Ураган-2М. Изучены конфигурации магнитного поля при различных соотношениях между винтовым и продольным магнитным полем 0.2 < Kφ < 0.6. Показано, что в случае больших значений параметра Kφ, когда замкнутая магнитная конфигурация полностью размещается внутри вакуумной камеры без пересечения со стенкой, следы уходящих силовых линий образуют на стенке камеры две винтовые линии, расположенные между полюсами винтовой обмотки. При малых значениях Kφ, когда замкнутая магнитная конфигурация пересекает стенку камеры, внешние силовые линии образуют широкую полосу, соответствующую винтовой линии, по которой проходит вершина магнитной конфигурации.